Normative values of intra‐bolus pressure and esophageal compliance based on 4D high‐resolution impedance manometry - Kou, Wenjun; Carlson, Dustin A.; Kahrilas, Peter J.; Patankar, Neelesh A.; Pandolfino, John E. (Neurogastroenterology and motility, 2022)
Background This study aimed to quantify normative values of phase‐specific intra‐bolus pressure (IBP) and esophageal distensibility using 4D analysis of high‐resolution‐impedance manometry (HRIM). Methods HRIM studies of supine swallows from 34 normal controls were analyzed with respect to the four phases of bolus transit: (1) accommodation, (2) compartmentalization, (3) peristalsis/esophageal emptying, and (4) ampullary emptying. Phase‐specific IBP, bolus volume, and distensibility index (DI) in the esophageal body and esophagogastric junction (EGJ) during phases 1–3 were extracted. Results The median (5‐95th/IQR) IBP values were as follows: phase 1: 4.0 (−2.0–10.4/1.9–5.8) mmHg, phase 2: 5.7 (0.2–14.1/3.6–8.9) mmHg, and phase 3: 11.2 (2.9–19.4/7.7–15.1) mmHg. The median bolus volume calculated by integrating impedance planimetry cross‐sectional areas was 4.1 ml during the compartmentalization phase. The EGJ‐DI at max EGJ diameter during phase 2 and 3 was 2.8 (1.1–9.5/1.8–3.7) mm2/mmHg and 6.0 (3.2–20.3/5.1–7.8) mm2/mmHg, respectively. The phase 3 EGJ‐DI values (6.0 (3.2–20.3/5.1–7.8) mm2/mmHg) were similar to those calculated using functional lumen imaging probe (FLIP) at the 60 ml volume on the same subjects (5.8 [3.5–7.2/5.0–6.4] mm2/mmHg). Conclusions and Inferences 4D‐HRIM provides a standardized methodology to track the nadir impedance and provide measurements of IBP during maximal distention across phases 1–3 of bolus transit. Median IBP and delta IBP were different across the phases, supporting the need to define IBP by phase. Additionally, the EGJ‐DI calculated during phase 3 was similar to the 60‐ml EGJ‐DI from FLIP in the same subjects suggesting that 4D‐HRIM can quantify EGJ opening during primary peristalsis. For 4D normal controls, intra‐bolus pressure was elevated from phase 1(P1) to phase 3(P3), and EGJ‐DI increased from P2 to P3.